Reading bodies, books, and beyond: experience and contingency in Troilus and Criseyde*. Issue 11 (2nd November 2022) - Buchanan, Peter
ABSTRACT: Chaucer's Troilus and Criseyde puts perspective itself under the microscope: throughout, the individual experience of reading the world is brought into the foreground as sense-perception, and the immediate experience of time, are rendered with a striking psychological verisimilitude. This essay breaks with the critical orthodoxy around this poem, which sees the poem's dynamics of temporal perspectives as a structural analogue with Boethius' philosophy of time and free will—one which places the reader 'in God's shoes' by providing advance knowledge of the poem's end. Challenging this notion, this essay argues that the poem's complex interplay of individual perspectives actually reveals the total contingency of the readerly vantage-point, exposing the 'situatedness in time' of reader and text. Rather than being a cipher for Boethian philosophy, I argue that Troilus and Criseyde advances a Chaucerian phenomenology of reading—one that is as metapoetic as it is metaphysical, concerning both semantic indeterminacy and the temporality of individual experience. This approach brings Chaucer into productive, and largely untapped, dialogues with modern philosophers and contemporary theoretical currents, including recent advances considering literature and contingency.